Thermo distillation and characterization of bio oil from fast pyrolysis of empty fruit bunch (EFB) / Deana Qarizada ... [et al.]. - Qarizada, Deana; Mohammadian, Erfan; Alias, Azil Bahari; Hassan, Zulkafli; Sabet, Maziyar (2017)
The demand for sustainable fuels on one hand and the shortage of conventional energy resources on the other hand, has led to the need for the development of alternative, environmentalfriendly fuels. Hence, the objectives of the current study were to produce a liquid fuel (bio-oil) from Empty fruit bunch (EFB) and to characterizes the bio oil by fast pyrolysis method, in a batch feeding and fixed bed reactor. The Temperature was set to 500°C for all the distillation experiments and the bio oil was collected from the condenser. The total yield of bio oil based on EFB was 66wt.%. The non-condensable gases obtained from the process were CO2, CO, CH4, C2H6, C2H4, C3H8 and C3H6. The higher heating value (HHV) was 27 MJ/Kg. The physical and chemical properties of the produced oil was also determined and discussed in this paper.The moisture, volatile mater and ash were determined and found to be around 1.4391wt %, 6.0182wt% and 1.3906wt%respectively.